A Novel Hollow‐Tube‐Biphasic‐Whisker‐Modified Calcium Phosphate Ceramics with Simultaneously Enhanced Mechanical Strength and Osteogenic Activity. (11th August 2022) - Feng, Cong; Wu, Yonghao; Li, Qipeng; He, Tinghan; Cao, Quanle; Li, Xiangfeng; Xiao, Yumei; Lin, Jiangli; Zhu, Xiangdong; Zhang, Xingdong
Abstract: Due to the inherent brittleness and low mechanical strength, it is still a challenge for calcium phosphate (Ca‐P) ceramics to be used in load‐bearing bone defect repair. To achieve a good balance between mechanical strength and osteogenic activity, hollow‐tube‐whisker‐modified biphasic calcium phosphate (BCP) ceramics (BCP‐HW) are successfully fabricated by an in situ growth process in the present study. Compared to the initial BCP ceramics (BCP‐C) and those with solid whiskers, BCP‐HW exhibits larger specific surface area (3.9 times vs BCP‐C) and higher mechanical strength (3.4 times vs BCP‐C), endowing it with stronger stimulation on adhesion, proliferation, and osteogenic differentiation of bone marrow mesenchymal stem cells. In an intramuscular implantation model of canine, BCP‐HW shows excellent osteoinductivity and promotes the maturation of new bone, and the resultant compressive strength of the implant increases to ≈12 MPa at 3 months postoperatively. In another critical‐sized segmental bone defect model of rabbit femur, BCP‐HW has the best repairing effect. After implantation for 6 months, much more new bone ingrowth and higher bending load are observed in BCP‐HW than BCP‐C. Collectively, these findings suggest that the in situ hollow‐tube whisker construction possesses immense potential in expanding the applications of Ca‐P ceramics to load‐bearing bone defect repair. Abstract : The present study introduces an effective approach to construct in situ hollow‐tube whiskers in biphasic calcium phosphate (BCP) ceramics and discusses the formation mechanism. The in situ hollow‐tube whiskers can endow BCP ceramics with excellent osteoinductivity and biomechanical properties. BCP bioceramics with hollow‐tube whiskers have great potential in the regenerative repairing of the load‐bearing bone defects.